PENYULUHAN PENTINGNY ASA YURAN BAGI ANAK-ANAK DI TK AISYIY AH KW ADUNGAN, TROW ANGSAN, MALANGJIW AN, COLOMADU, KARANGANY AR, JA WA TENGAH - Ichsan, Burhannudin; Wibowo, Bayu Hendro; Sidiq, M. Nur (WARTA, 2015)
Kindergarten children is a phase of school children. School children phase generally  have  better  condition  than  children  under  five  years,  because  many government programs can be targeted at these groups, that one of them is the UKS programs  (Program  Usaha  Kesehatan  Sekolah),  but  the  program  has  not  been prevalent at kindergarten school generally. A frequent problem faced by the children of this phase is difficult to eat, especially vegetables because they do not have a sweet taste. There are a variety of nutritional conditions that are unsatisfactory at schoolchildren, for example, less weight, iron deficiency anemia, a deficiency of vitamin C, and in certain areas also lack of jodium. Lack of vegetables are things that can cause vitamin and mineral deficiencies. Authors do counseling about the importance of vegetables  for  children  in  kindergarten  Aisyiyah,  Kwadungan,  Trowangsan, Malangjiwan, Colomadu to convey the importance of vegetables so that the parents have a stronger effort to encourage their children to consume vegetables. Counseling is done by the power point media and done interactively. Authors gave pre-test andpost-test regarding knowledge about the importance of vegetables. There were prizes for the highest score of the post-test to attract participants. Paired samples t test was performed with the result that there was a significant increase in knowledge (p =0.000) in the parents.